PREVALENSI ANEMIA PADA KEHAMILAN : SEBUAH TINJAUAN LITERATUR SISTEMATIS - Azmira, Nazurah; Defrin, Defrin; Burhan, Ida Rahmah; Rustam, Erlina; Antonius, Puja Agung; Yusri, Elfira (SINERGI : Jurnal Riset Ilmiah, 2025)
Background : Anemia has become a public health problem that bring many potencial danger to both maternal and neonatal side. Many studies show that there are significant correlation between maternal mortality and anemia during pregnancy.Objective: This review is done to determine the prevalence and risk factors of anemia among pregnant women Methods : This study is a systematic literature review focused on the prevalence of anemia during pregnancy from 2011-2020. Literature search on Pubmed and Proquest databases was carried out to identify studies included in inclusion criteria related to prevalence of anemia during pregnancy. In this review, 60 articles were reviewed after 4105 articles found in both databases were screened using PRISMA guidelines. A total of 49589 participants from 20 developing countries were included. Results : The results showed that the rate of anemia in pregnancy range from 7,4% to 90%, with an average of 36,2%. The most reported risk factors are low economic level/ household income (10,2%), maternal age (9,6), rural residence (7,8%), educational status of the mother (7,2%)and less consumption of iron/folic acid (7,2%). Conclusion : Based on the review, available evidence suggest that prevalence of anemia remain high especially in low and middle income countries. Maximum efforts need to be initiated to help prevent anemia during pregnancies. Public should be educated on early initiation of antenatal care to enhance surveillance, identification and treatment of anemia